Everybody’s Happy Nowadays? A Critical Engagement with Key Events and Contemporary Quests for the Historical Jesus - Crossley, James G. 1973- (2014)
Key Events is clearly a major contribution to historical Jesus studies from a broadly evangelical perspective. While there is much to commend and a number of strong essays, there are, inevitably criticisms to be made. A number of arguments appear to be repeating debates from the 1980s and 1990s with a familiar cast of good (e.g. N.T. Wright), bad (e.g. Burton Mack, Jesus Seminar) and ambivalent (e.g. E.P. Sanders) characters. This nostalgic feel means that alternative understandings of the historical Jesus and wider issues of history and historical change are not properly discussed, although clearly the opportunities were present among the contributors of Key Events. There is a sustained discussion of historical change in the chapter on resurrection but this repeats problematic arguments in favour of the historicity of the resurrection in what is effectively an attempt to prove what is historically unprovable. Finally, to lesser or greater extent, a number of essays in Key Events continue to perpetuate the idea of a ‘Jewish … but not that Jewish’ Jesus through monolithic constructions of Jews and Judaism and through the discredited criterion of dissimilarity in disguise: double dissimilarity. It is not always clear that the problematic criterion of double dissimilarity is applied consistently, with some evidence of contributors forgetting aspects of dissimilarity from Christianity while never forgetting dissimilarity from Judaism (even when similar Jewish evidence is, in fact, available). These criticisms should not take away from a number of positive contributions made to historical Jesus studies and it may be that Key Events represents a vision of what most historical Jesus scholars see as the future of the sub-field.
Keywords: Key Events in the Life of the Historical Jesus -- resurrection of Jesus -- historiography -- Jewishness of Jesus -- dissimilarity and double dissimilarity